Answers

2014-09-30T17:44:45+05:30
Let peter's age be " x "
Let Paul's present age be "y"
Let z be the no of years indicated as "when" in the question
(x - z) = peter's age z years ago
(y - z) = paul's age z years ago

(x + y) = 35

z years ago peter was ( x - z ) and that is the age of Paul is now, so

x - y = z

but Paul was (y - z)

As peter is now twice the age of paul's age then

x = 2(y - z)
x= 2y - 2z

so, the equations we have are

(x + y) = 35
x - z = y
x = 2y - 2z

lining them all,

x  + y = 35
x - y - z = 0
x - 2y - 2z = 0

so, solving this we get

x = 20
y = 15
z = 5

so peter's age = 20 years








0
2014-10-02T00:24:13+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let present age of peter = x
                             paul = y

x+y = 35    and
x= 2(y-(x-y))
⇒x = 4y - 2x
⇒3x =4y
⇒x = 4y/3

7y/3 = 35
⇒y = 15 yrs (paul's age)
x = 4×15/3 = 20 (peter's age)

0